A one-step solvothermal synthesis of the topological insulator Bi2Te3 nanorod-modified TiO2 photocatalyst for enhanced H2-evolution activity. Issue 16 (4th April 2022) - Dong, Lin; Wang, Xuefei; Wang, Ping; Yu, Huogen
Abstract : Topological insulator Bi2 Te3 nanorods as effective cocatalysts were modified on a TiO2 surface by an EG-assisted solvothermal method to improve the photocatalytic H2 -evolution activity of TiO2 due to their high conductivity and suitable Te–H bond. Abstract : Bismuth sulfide (Bi2 S3 ) as a cocatalyst shows a limited photocatalytic H2 evolution performance due to its low conductivity and strong S–H bond, which is not beneficial to the transmission of photoexcited electrons and hydrogen desorption. Therefore, it is very important to explore new Bi-based cocatalysts with high conductivity and appropriate hydrogen adsorption–desorption ability. In this work, the topological insulator Bi2 Te3 nanorods worked as an effective cocatalyst to facilitate the photocatalytic H2 -evolution activity of TiO2 because of its high conductivity and suitable Te–H bond. Bi2 Te3 nanorod modified-TiO2 (Bi2 Te3 /TiO2 ) has been successfully prepared by a one-step EG-assisted solvothermal method. The H2 -evolution results showed that the Bi2 Te3 /TiO2 (0.5 wt%) sample reached a high photocatalytic hydrogen-generation performance (1494 μmol h −1 g −1, AQE = 7.18%), which is 143.7, 3.0 and 1.2 times those of TiO2, Bi2 S3 /TiO2 (0.5 wt%), and Bi2 Se3 /TiO2 (0.5 wt%), respectively. The boosted photocatalytic H2 -generation activity can be ascribed to the synergistic effect of topological insulator Bi2 Te3 as an electron transport medium to rapidly transfer electrons owing to its highly conducting surface states and Te atoms as high-efficiency H2 -generation sites to accelerate the H2 -generation reaction due to appropriate Te–H bond. This paper affords a new insight for exploiting novel Bi-based cocatalysts to further enhance the photocatalytic hydrogen-production efficiency of photocatalysts.